ANALISIS KOMPARASI KINERJA SAHAM YANG TERDAFTAR DI JAKARTA ISLAMIC INDEKS SEBELUM DAN SELAMA PANDEMI COVID 19 - Wahid Wachyu Adi Winarto (Universitas Muhammadiyah Surakarta, 2021)
This research aims to test and empirically analyze industrial performance as reflected in the performance of stocks listed in the Jakarta Islamic Index using the risk adjusted return ratio, Sharpe, Treynor and Jensen alpha.Analysis for hypothesis testing using purposive sampling method. The population in this research is all sharia indexes listed on the Jakarta Islamic Index (JII) in Indonesia. The period of research information that is the object of this research is the weekly return index from April 2019 to December 2020, totaling 44 information, the information is differentiated between the time before and during the Covid 19 pandemic. Hypothesis testing uses two different tests of independent sample means use Risk adjusted return, Sharpe, treynor and Jensen alpha. The results showed that the ratio of risk adjusted return, Sharpe, Treynor and Jensen alpha, there was no significant difference in performance between before and during the Covid 19 pandemic.